A Multimodal Study of How Pronunciation-Induced Communication Breakdowns are Managed During Tandem Interactions - Loulou Kosmala; Céline Horgues; Sylwia Scheuer (Research in Language)
This paper offers quantitative and qualitative findings from the exploration of communication breakdowns in English tandem interactions, by adopting a multimodal perspective. It focuses on the ways in which pronunciation-induced CBs are managed by language peers in a tandem setting. This study shows cases where it was the non-native participant’s output that was the main communicative stumbling block, with a view to reporting on pronunciation-induced breakdowns. More specifically, our analyses target the ways in which CBs are signaled to the interlocutor with different multimodal cues (verbal / vocal / visual). Those pronunciation issues are dealt with in a highly collaborative manner, through multimodal communication strategies, revealing recurrent visual patterns involving different visible body articulators (i.e., the face, the trunk, and the hands) which differ according to participants’ status (native versus non-native).